The application and sustainable development of coral in traditional medicine and its chemical composition, pharmacology, toxicology, and clinical research - Han, Mengtian; Wang, Zhongyuan; Li, Yiye; Song, Yinglian; Wang, Zhang (Frontiers in Pharmacology, 2024)
This review discusses the variety, chemical composition, pharmacological effects, toxicology, and clinical research of corals used in traditional medicine in the past two decades. At present, several types of medicinal coral resources are identified, which are used in 56 formulas such as traditional Chinese medicine, Tibetan medicine, Mongolian medicine, and Uyghur medicine. A total of 34 families and 99 genera of corals are involved in medical research, with the Alcyoniidae family and Sarcophyton genus being the main research objects. Based on the structural types of compounds and the families and genera of corals, this review summarizes the compounds primarily reported during the period, including terpenoids, steroids, nitrogen-containing compounds, and other terpenoids dominated by sesquiterpene and diterpenes. The biological activities of coral include cytotoxicity (antitumor and anticancer), anti-inflammatory, analgesic, antibacterial, antiviral, immunosuppressive, antioxidant, and neurological properties, and a detailed summary of the mechanisms underlying these activities or related targets is provided. Coral toxicity mostly occurs in the marine ornamental soft coral Zoanthidae family, with palytoxin as the main toxic compound. In addition, nonpeptide neurotoxins are extracted from aquatic corals. The compatibility of coral-related preparations did not show significant acute toxicity, but if used for a long time, it will still cause toxicity to the liver, kidneys, lungs, and other internal organs in a dose-dependent manner. In clinical applications, individual application of coral is often used as a substitute for orthopedic materials to treat diseases such as bone defects and bone hyperplasia. Second, coral is primarily available in the form of compound preparations, such as Ershiwuwei Shanhu pills and Shanhu Qishiwei pills, which are widely used in the treatment of neurological diseases such as migraine, primary headache, epilepsy, cerebral infarction, hypertension, and other cardiovascular and cerebrovascular diseases. It is undeniable that the effectiveness of coral research has exacerbated the endangered status of corals. Therefore, there should be no distinction between the advantages and disadvantages of listed endangered species, and it is imperative to completely prohibit their use and provide equal protection to help them recover to their normal numbers. This article can provide some reference for research on coral chemical composition, biological activity, chemical ecology, and the discovery of marine drug lead compounds. At the same time, it calls for people to protect endangered corals from the perspectives of prohibition, substitution, and synthesis.